The attitudes of academics to accomodating physically disabled students into the undergraduate civil engineering programme in the Faculty of Engineering and Science, University of KwaZulu-Natal - Mayat, Nafisa (Department of Health and Rehabilitation Sciences, 2014)
Includes bibliographical references (leaves 54-61).